The Connection Between Students Mental Capacity and Learning Outcome in Secondary Schools (Journal of Didactic Studies, 2024)
The aim of this study is to examine the connection between students’ mental capacity and learning outcome in secondary schools. Learning outcome is the result of education in which student, teacher or institution were able to derived their educational aims and objectives. The participant for this study will comprises of 190 teachers in secondary schools in education district 1. The research design for this study was correlational research design type. Data Were Collected Using The "Students Mental Capacities, And Learning Outcome Questionnaire" (SMCLOQ). The mean score of students with mental capacity was higher, so teacher needs to concentrate on students whose learning outcome is low and use different teaching materials and methods, the teachers should teach according to the capacities of students which will assist the students to be successful. Learning outcomes and student’s mental capacity are significantly related, so schools needs to support the students to develop their mental capacities.